Особливості системної гемодинаміки, вегетативного забезпечення, агрегації тромбоцитів у хворих на гіпертонічну хворобу високого та дуже високого ризику, лікування та прогноз - Жеманюк, Світлана Павлівна; Жеманюк, С. П.; Zhemanyuk, S. P. (Запорізький державний медичний університет, 2020)
Робота присвячена удосконаленню методів діагностики і контролю артеріального тиску (АТ) у хворих на гіпертонічну хворобу (ГХ) з неконтрольованим АТ та з ускладненим (ішемічним півкульним інсультом) перебігом, а також індивідуалізації антигіпертензивної терапії. Обстежено 254 особи (60 (54; 70) років). У хворих на ГХ з контрольованим (n=43), неконтрольованим (n=102) АТ, з ускладненим перебігом (n=34) на фоні антигіпертензивної терапії і практично здорових осіб (n=13) досліджено показники добового моніторування АТ, варіабельності ритму серця, агрегації тромбоцитів (результати 62 особи виключено). Встановлено фактори, асоційовані з недосягненням цільового АТ (середньогемодинамічний і пульсовий АТ, індекс площі нормалізований діастолічного АТ) та пов’язані з ускладненим перебігом (середньогемодинамічний АТ, SDNN, площа під кривою першої хвилини адреналін-індукованої агрегації тромбоцитів). Доведено, що найбільш ефективною в досягненні цільового АТ у хворих на ГХ є багатокомпонентна антигіпертензивна терапія (ІАПФ / БРА, діуретик, β-адреноблокатор). У хворих на ГХ з ускладненим перебігом в досягненні цільового АТ в короткостроковому періоді однаково ефективні одно- і багатокомпонентна антигіпертензивна терапія. Работа посвящена усовершенствованию диагностики и контроля артериального давления (АД) больных гипертонической болезнью (ГБ) с неконтролируемым АД, осложненным (ишемическим полушарным инсультом) течением, индивидуализации антигипертензивной терапии. Обследовано 254 человека (60 (54; 70) лет). У больных ГБ с контролируемым (n=43), неконтролируемым (n=102) АД, осложненным течением (n=34) на антигипертензивной терапии и практически здоровых лиц (n=13) проведено суточное мониторирование АД, вариабельность ритма сердца, агрегация тромбоцитов (результаты 62 человека исключены). Определены факторы, ассоциированные с недостижением целевого АД (среднее гемодинамическое и пульсовое АД, индекс площади нормированный диастолического АД) и осложненным течением (среднее гемодинамическое АД, SDNN, площадь под кривой за первую минуту адреналин-индуцированной агрегации тромбоцитов). Доказано, что наиболее эффективной в достижении целевого АД у больных ГБ является многокомпонентная антигипертензивная терапия (ИАПФ / БРА, диуретик, β-адреноблокатор). У больных ГБ с осложненным течением в достижении целевого АД в краткосрочном периоде эффективны в равной степени одно- и многокомпонентная антигипертензивная терапия. Thesis is devoted to improvement of blood pressure (ВР) diagnostic and control methods in essential hypertension patients (EНs) by studying clinical and pathogenic characteristics as systemic hemodynamic, vegetative balance and platelet induced (epinephrine and ADF) aggregation activity changes associated with uncontrolled BP, acute (ischemic hemispheric) stroke, as well as individualizing antihypertensive therapy considering the components of ambulatory BP monitoring (ABPM). As the result, 254 individuals (60 (54; 70) years) were inspected. After establishment of accordance to the criteria of including / exception, ABPM, heart rate variability (HRV), platelet analysis and 62 subjects exclusion, four groups were formed: the 1st and 2nd included on antihypertension treatment EHs controlled (n=43) and uncontrolled BP (by ABPM) EHs (n=102), respectively; the 3d group – acute stroke in-treated EHs (verified by tomography) inspected twice (on the 3 (2; 5) and 21 (12; 30) day, n=34); the 4d – healthy persons without arterial hypertension (n=13). It has been established that systemic hemodynamic by ABPM detecting in controlled EHs was enlarged in morning and daily hours compared with healthy individuals. At the same time, uncontrolled and controlled EHs had no differences in arterial stiffness indexes and BP variability. The systemic hemodynamic in acute stroke EHs vs uncontrolled EHs was increased in night, prewakening-morning hours and decreased in daytime. There was an enhanced parasympathetic activity detecting by long-term HRV in EHs regardless the BP level. There was a reduction of total HRV with an increase of sympathetic activity and decrease of parasympathetic in acute stroke EHs. Platelet ADF-activity in controlled EHs (vs healthy individuals) and in acute stroke EHs (vs uncontrolled EHs) was elevated, while epinephrine-induced platelet aggregation was suppressed. Uncontrolled and controlled EHs had the epinephrine-induced aggregation’s level the same, however, the former had the prominent inhibition of ADF-induced aggregation. Age-, sex- and diabetes-adjusted factors associated with uncontrolled BP in EHs were diurnal mean arterial pressure (Wezler-Bögerr formula), pulse pressure, square load normalized diastolic BP. The prognosis model of acute stroke EHs included diurnal mean arterial pressure (Wezler-Bögerr formula) and SDNN, the square under the epinephrine-induced platelet aggregation the first minute curve as age-, sex- and diabetes-adjusted model’s factors. The most effective antihypertension therapy to control BP in EHs was usage of ACE inhibitors / ARBs, diuretics and β-blockers. As monotherapy, as well as complex antihypertensive therapy showed effectiveness in the short term lowering BP in acute stroke EHs.
Особенности системной гемодинамики, вегетативного обеспечения, агрегации тромбоцитов у больных гипертонической болезнью высокого и очень высокого риска, лечение и прогноз
Systemic hemodynamic, autonomic nervous regulation, platelet aggregation patterns in essential hypertension patients with high and very high risk, treatment and prognosis
Keywords: гіпертонічна хвороба; артеріальний тиск; варіабельність ритму серця; агрегація тромбоцитів; прогностичні фактори; гипертоническая болезнь; артериальное давление; вариабельность ритма сердца; агрегация тромбоцитов; прогностические факторы; essential hypertension; blood pressure; heart rate variability; platelet aggregation; predictors